Application of Data Mining to Predict and Diagnose Diabetic Retinopathy - Haniyeh, Maryam (2024)
A Master of Science thesis in Biomedical Engineering by Maryam Haniyeh entitled, “Application of Data Mining to Predict and Diagnose Diabetic Retinopathy”, submitted in June 2024. Thesis advisor is Dr. Michel Pasquier and thesis co-advisor is Dr. Assim Sagahyroon. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).